THE DISSOLUTION-PRECIPITATION KINETICS OF CALCIUM-CARBONATE - AN ASSESSMENT OF VARIOUS KINETIC-EQUATIONS USING A ROTATING-DISK METHOD - Compton, R; Daly, P (1987)
The dissolution/precipitation kinetics of calcium carbonate has been studied using a rotating disk technique. A crystal of Iceland Spar was allowed to dissolve in water until equilibrium was established and the solution thus saturated with CaCO3. The Ca2+ concentration was monitored throughout the period of dissolution using a calcium ion selective electrode. In this way various kinetic equations proposed by different workers to describe the dissolution/precipitation process have been tested. In particular it is found that the equation of Sjoberg, rateS = kS{Ksp 1 2 - [Ca2+] 1 2[CO32-] 1 2}, where Ksp is the solubility product, and the equation of Plummer, rateP = kP3 - kP4[Ca2+][HCO3-], both give excellent fits to the observed data. In contrast, the equations of Davies and Jones and of Dorange and Guetchidjan are unsatisfactory. © 1987.